2022
DOI: 10.1038/s41598-021-04356-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age at onset on symptom profiles, treatment characteristics and health-related quality of life in Parkinson’s disease

Abstract: Parkinson’s disease (PD) is typically considered an age-related disease, but the age at disease onset can vary by decades between patients. Aging and aging-associated diseases can affect the movement system independently of PD, and advanced age has previously been proposed to be associated with a more severe PD phenotype with accelerated progression. In this work, we investigated how interactions between PD progression and aging affect a wide range of outcomes related to PD motor and nonmotor symptoms as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Therefore, the current study aimed to use the modified DTI‐ALPS method to explore the glymphatic activity and its related factors, including the severity of motor and non‐motor symptoms in PD patients. Age has been reported to be associated with different PD phenotypes by previous studies, 6,7 underpins which we hypothesized that glymphatic function plays different roles in the pathogenesis and progression of PD among patients of different age groups. So, associations between ALPS index and disease severity in PD patients of different age groups were also explored.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, the current study aimed to use the modified DTI‐ALPS method to explore the glymphatic activity and its related factors, including the severity of motor and non‐motor symptoms in PD patients. Age has been reported to be associated with different PD phenotypes by previous studies, 6,7 underpins which we hypothesized that glymphatic function plays different roles in the pathogenesis and progression of PD among patients of different age groups. So, associations between ALPS index and disease severity in PD patients of different age groups were also explored.…”
Section: Introductionmentioning
confidence: 93%
“…And it has been reported that the accumulation of α‐syn in the brain is greatly related to age 5 . However, the underlying mechanism between aging and the pathogenesis and progression of PD is poorly understood 6–8 …”
Section: Introductionmentioning
confidence: 99%
“…Aging is a well known factor for PD [53][54][55][56] . Hence, it is common to detect gene modules associated with PD diagnosis and their age simultaneously (see results).…”
Section: Gene Segregation Based On Covariatesmentioning
confidence: 99%
“…There have been recent efforts to better define the different forms of the disease based on specifics of motor and non-motor features, age of disease onset and pathology. This has been explored extensively elsewhere ( Greenland et al, 2019 ; Raket et al, 2022 ), but, pertinent to this Review, many of the clinical transplantation studies ( Table 1 ) occurred prior to any clear differentiation of specific PD phenotypes.
Box 1.
…”
Section: Introductionmentioning
confidence: 99%